A fronto-parietal system for computing the egocentric spatial frame of reference in humans - Vallar, Giuseppe; Lobel, Elie; Galati, Gaspare; Berthoz, Alain; Pizzamiglio, Luigi; Le Bihan, Denis (Experimental brain research, 1999)
Spatial orientation is based on coordinates referring to the subject's body. A fundamental principle is the mid-sagittal plane, which divides the body and space into the left and right sides. Its neural bases were investigated by functional magnetic resonance imaging (fMRI). Seven normal subjects pressed a button when a vertical bar, moving horizontally, crossed the subjective mid-sagittal plane. In the control condition, the subjects' task was to press a button when the direction of the bar movement changed, at the end of each leftward or rightward movement. The task involving the computation of the mid-sagittal plane yielded increased signal in posterior parietal and lateral frontal premotor regions, with a more extensive activation in the right cerebral hemisphere. This direct evidence in normal human subjects that a bilateral, mainly right hemisphere-based, cortical network is active during the computation of the egocentric reference is consistent with neuropsychological studies in patients with unilateral cerebral lesions. Damage to the right hemisphere, more frequently to the posterior-inferior parietal region, may bring about a neglect syndrome of the contralesional, left side of space, including a major rightward displacement of the subjective mid-sagittal plane. The existence of a posterior parietal-lateral premotor frontal network concerned with egocentric spatial reference frames is also in line with neurophysiological studies in the monkey.